Characterization of Indian Rice (Oryza sativa L.) Varieties based on Seed Morphology and Phenol Colour Test - VIBHA KHANDELWAL; S.K. CHAKRABARTY; MALAVIKA DADLANI; S.P. SHARMA (Seed Research, 2026)
Characterization of 58 released Indian rice (Oryza sativa L.) varieties was done using seed morphological characteristics, viz, length, width, colour, shape, presence or absence of awn and phenol colour reaction. Twenty-six varieties were distinguishable individually and the rest were classified into discrete groups. The seed morphological characters based on IRRI and UPOV guidelines including kernel colour and grain length were compared. Phenol colour test, performed on seed from two years and harvest at different locations, confirmed that a specific colour reaction is predominant in each variety, though variation in the intensity of the colour was noticed. A reliable application of positive and negative colour response is suggested. Results suggested that prior to field based testing, these simple laboratory tests could provide for rapid grouping and facilitate verification of a large numbers of rice varieties.